Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Spagnol, Stephen T.; Lin, Wei Chun; Booth, Elizabeth A.; Ladoux, Benoit; Lazarus, Hillard M.; Dahl, Kris Noel (Annals of Biomedical Engineering, 2016)
The cellular structures and mechanical properties of human mesenchymal stem cells (hMSCs) vary significantly during culture and with differentiation. Previously, studies to measure mechanics have provided divergent results using different quantitative parameters and mechanical models of deformation. Here, we examine hMSCs prepared for clinical use and subject them to mechanical testing conducive to the relevant deformability associated with clinical injection procedures. Micropipette aspiration of hMSCs shows deformation as a viscoelastic fluid, with little variation from cell to cell within a population. After two passages, hMSCs deform as viscoelastic solids. Further, for clinical applicability during stem cell migration in vivo, we investigated the ability of hMSCs to invade into micropillar arrays of increasing confinement from 12 to 8 μm spacing between adjacent micropillars. We find that hMSC samples with reduced deformability and cells that are more solid-like with passage are more easily able to enter the micropillar arrays. Increased cell fluidity is an advantage for injection procedures and optimization of cell selection based on mechanical properties may enhance efficacy of injected hMSC populations. However, the ability to invade and migrate within tight interstitial spaces appears to be increased with a more solidified cytoskeleton, likely from increased force generation and contractility. Thus, there may be a balance between optimal injection survival and in situ tissue invasion.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell mechanics; Human mesenchymal stem cells; Mechanobiology; Micropipette aspiration